TANGGUNG JAWAB LEMBAGA PEMASYARAKATAN DALAM PEMBINAAN NARAPIDANA UNTUK MENCEGAH DAN MEMINIMALISASI RESIDIVIS DI LEMBAGA PEMASYARAKATAN KELAS II A PEKANBARU - teguh eka putra; Firdaus Firdaus; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The guidance carried out by the Class II Penitentiary in Pekanbaru,namely welding, barbershop, rattan making services, narista, motorcycle service,processing organic nuggets, processing soybeans, reflexy massage, hydroponicvegetables, , lack of budget, and the less than optimal capacity or area of theClass II a Penitentiary in Pekanbaru.This research is using research method that is a sociological legalresearch. Sociological legal research is legal research that looks at how it shouldbe (dass solen) and what the facts are in the field (dass sein). This study looks athow coaching in Class II a Pekanbaru prisons should be, but in fact the coachingis not carried out as it should.The results of this study, in conducting coaching at the Pekanbaru Class IIA Prison, there are still shortcomings carried out by the Pekanbaru Class II APrison, such as a shortage of personnel, budget and capacity shortages or the sizeof the Class II a Pekanbaru Penitentiary. Efforts that need to be carried out areadding personnel, increasing the budget and expanding the capacity or area ofthe Class II a Penitentiary in Pekanbaru. So it is hoped that the guidance can bemaximized and can reduce inmates who have been inmates from committingcrimes again (recidivists).Keywords: Correctional Institution – Inmates – Guidance.